2018
DOI: 10.1021/acssuschemeng.8b02881
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Different Biochars in Removing Odorous Volatile Organic Compounds (VOCs) Emitted from Swine Manure

Abstract: The potential of various biochars to remove 15 odorous volatile organic compounds emitted from swine manure were investigated via laboratory sorption experiments. Nine biochars made from pyrolyzing poultry litter, swine manure, oak, and coconut shell at 350 °C and 500 °C and a commercial coconut-shell activated carbon were evaluated for their sorption capacities toward the odorous compounds. These 15 odorous volatile organic compounds (VOCs) consisted of reduced sulfur compounds, volatile fatty acids, phenolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…The concentrations of odorous VOCs in the influent and effluent streams were measured using thermal desorption sorbent tubes similar to Hwang et al [18]. Influent and effluent gas samples were pulled and passed through the sorbent tubes (Markes International, #C1-AAXX-5003, Sacramento, CA, USA) at 75 mL/min for a duration of 20 min (i.e., 1.5 L of a total sample volume) using small pumps (SKC, #210-1002 pocket pump and #220-5000TC Aircheck Touch, Eighty Four, PA, USA).…”
Section: Analyses Of Odorous Vocs H 2 S and Scoavsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations of odorous VOCs in the influent and effluent streams were measured using thermal desorption sorbent tubes similar to Hwang et al [18]. Influent and effluent gas samples were pulled and passed through the sorbent tubes (Markes International, #C1-AAXX-5003, Sacramento, CA, USA) at 75 mL/min for a duration of 20 min (i.e., 1.5 L of a total sample volume) using small pumps (SKC, #210-1002 pocket pump and #220-5000TC Aircheck Touch, Eighty Four, PA, USA).…”
Section: Analyses Of Odorous Vocs H 2 S and Scoavsmentioning
confidence: 99%
“…Biochar is a carbonaceous product of pyrolyzing biomass with the potential to improve soil quality and water holding capacities [17]. Recently, Hwang et al evaluated the potential of using biochar made from animal manure and plant biomass for removing 15 odorous volatile organic compounds (VOCs) which consisted of reduced sulfur compounds, volatile fatty acids, phenolic, and indolic compounds [18]. They found that manure-based biochars could not effectively remove reduced sulfur compounds such as dimethyl disulfide (DMDS) and dimethyl trisulfide (DMTS).…”
Section: Introductionmentioning
confidence: 99%
“…Odor strength of each compound was determined by OAV (Parker et al, 2012;Trabue et al, 2016). Although OAV does not account for accurate hedonic tone of many odorous compounds in the air, it can be inferred as a rough estimation of relative concentrations of each odorous compound or class of compounds (Hwang et al, 2018). Total volatile organic compound (VOC) OAV was calculated by summing of each compound class OAV, which was used to evaluate the effect of manure dilution on odor.…”
Section: Headspace Gas Concentrationmentioning
confidence: 99%
“…In addition, modified biochar-based materials can also be used to mitigate the malodourous air caused by volatile organic compounds generated from municipal waste [21]. The biochar was also effective in diminishing the odorous compounds from livestock farming [22,23].…”
Section: Introductionmentioning
confidence: 99%